Stercoral Perforation Requiring Subtotal Colectomy in a Patient on Methadone Maintenance Therapy - A. Sakharpe; Y. K. Lee; G. Park; V. Dy (Case Reports in Surgery)
Stercoral perforation of the colon is a rare but serious complication of chronic constipation. We present a case of stercoral perforation requiring subtotal colectomy in a 41-year-old female who had been on methadone maintenance for a history of long-term intravenous heroin use. Our case highlights the importance of prompt and thorough surgical intervention in the successful treatment of this rare condition.